1996
DOI: 10.1136/jnnp.60.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic syringomyelia (cystic myelopathy): a prospective study of 449 patients with spinal cord injury.

Abstract: Objectives-To assess the incidence of post-traumatic syringomyelia (PTS) Materials and methods Four hundred and forty nine paraplegic and tetraplegic patients were admitted from within four hours to up to three weeks after injury and followed up up until 1 July 1994. Most of these patients had been seen clinically at least once a year. Conventional radiographs of the injured spine were performed before each MRI study. Kyphosis angle of the spine was measured taking the inferior end plate of the first unbroken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(85 citation statements)
references
References 28 publications
2
83
0
Order By: Relevance
“…The widely evoked role of persistent bony compression 8 ± 10 has been demonstrated in a recent study 5 which correlates the occurrence of syrinx in 20 cases with kyphosis. In the latter, 5 two patients with PTS underwent vertebral realignment, which was followed by collapse of the syrinxes.…”
Section: Radiological Analysis Of the Lesion Sitementioning
confidence: 82%
See 2 more Smart Citations
“…The widely evoked role of persistent bony compression 8 ± 10 has been demonstrated in a recent study 5 which correlates the occurrence of syrinx in 20 cases with kyphosis. In the latter, 5 two patients with PTS underwent vertebral realignment, which was followed by collapse of the syrinxes.…”
Section: Radiological Analysis Of the Lesion Sitementioning
confidence: 82%
“…In the latter, 5 two patients with PTS underwent vertebral realignment, which was followed by collapse of the syrinxes. Similarly, Sgouros and Williams 28 showed the e ectiveness in all cases of a laminectomy associated with opening of the subarachnoid space on the treatment of the syrinx.…”
Section: Radiological Analysis Of the Lesion Sitementioning
confidence: 99%
See 1 more Smart Citation
“…3 MRI has been found to be the most sensitive diagnostic imaging technique, and also yields information on the morphology of spinal cord cysts. On all imaging sequences, a spinal cord cyst should have a signal intensity equivalent to that of CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Syringomyelia was first described by Bastian in 1867, 1 and, in 1880, Stru?mpell et al 2 reported instances of syringomyelia following spinal cord injury. 3 The clinical incidence of post-traumatic syringomyelia in patients with spinal cord injury has been estimated at 0.3-3.2%, although the incidence recorded radiologically and at autopsy appears to be higher than the clinical incidence. 4,5 The increased use of magnetic resonance imaging (MRI) for diagnosis has caused post-traumatic syringomyelia to be reported in 12-22% of patients with spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%